Educational and Axiological Aspects of the Teacher's Mission - Wojciech Osial (Nicolaus Copernicus University in Toruń, 2012)
The subject is part of a broader context of reflection on values-based education in Polish schools. The problem is presented as a very current and important issue. The author assumes that today there is a strong need for concern for the educational function of schools, which seems to be in crisis. This kind of opinion can be seen in several places of the text. The article can be viewed as a kind of contribution towards the reflection on the need for values in education. The subject of values is analysed in relation to certain aspects of educational reality. First, the focus is on the the important role of the educational and formative dimension of schools. The author concludes that schools' mission is not limited to teaching but should also include educating and nurturing. He notes that the educational function of schools is not easy to implement. Among various difficulties, he mentions the influence of ideology and politics. Next, the issues of education based on values, especially the moral and social values, are presented. The author emphasizes the great influence of religious pedagogy and Christian education. Finally, the last point discusses how important it is for teachers to personally exemplify values. The final conclusion of the reflection leads us in the following direction: one of the main factors for the effectiveness of values-based education is the attitude and conduct of teachers.